PENDEKATAN SISTEM SEBAGAI KONSEP MAQASHID SYARIAH DALAM PERSPEKTIF JASER AUDAH - Miskari de Ahmad (Al-Maslahah : Jurnal Ilmu Syariah, 2018)
Abstract This study will discuss the thoughts of Jaser Audah who tried to study Islamic law in various dimensions, which was then called a multidisciplinary approach. The multi-disciplinary approach encompasses established aspects of methodology formulated by past ulemas, such as usul fiqh, fiqh, interpretation science, etc. In addition, the philosophical approach and systems theory became the most significant approach in establishing Islamic law. This maqashid sharia approach is then known as the system approach formulated by Jaser Audah, namely a fiqh theory approach that is holistic and does not limit the text or legal parity. But it refers more to the principles of Islamic sharia as a universal goal. Jaser Audah also divided Islamic legal thinking into three groups, namely Tardisionalis, Modernist, and Post-modernist. These three groups have not answered contemporary issues appropriately, so Islamic law is still fragile, closed, apologetic, and fixated on verbal arguments. The theory resulting from Jaser Audah's research is the validation of several ijtihad methodologies that have been agreed upon as a realization of the maqasid syari'ah. Practically this research produces Islamic rules that are conducive to the values of justice, moral behavior, nobility of mind, respect, common life, and the development of humanity, which is the meaning of maqasid syari'ah. The system approach is carried out through several steps, namely: first, validating all knowledge, second, using holistic principles, third, courage to open up and do renewal, fourth, measure qat'i and ta'arud in terms of availability of supporting evidence and determination of priority scale based on existing social conditions and not from the verbality of the text, and fifth, taking maqashid as the determination of Islamic law. Keyword : Jaser Audah, Islamic Law, Maqashid Syariah